Formative Assessment Practices Using a Culturally Responsive Teaching (CRT) Approach in the Context of Mie Des in Science Learning - Murniningsih Murniningsih; Ani Widyawati; Markhaban Alkhasni; Fadhil Syafri Praditya (Universitas Negeri Semarang, 2025)
This study aims to describe the implementation of formative assessment using the Culturally Responsive Teaching approach by integrating Mie Des as a local cultural context in science learning and to examine students’ responses to this practice. Using a descriptive qualitative design, data were collected through classroom observations, interviews, and documentation during three learning sessions on heat transfer. The results show that formative assessment was implemented through open-ended questions, reflections, group discussions, rapid and constructive feedback, the use of student worksheets, and the use of digital media. These activities helped students connect scientific ideas with their cultural experiences, increased their engagement, and strengthened their confidence in learning science. Students demonstrated active participation and emotional involvement, although some focused more on cultural aspects than scientific reasoning. The study concludes that integrating local culture into formative assessment can enhance scientific understanding, cultural awareness, and student engagement, while providing valuable feedback for designing responsive and contextually meaningful science learning.